THU0121 Do the Immunological and Ultrasound Characteristics Reflect the Clinical Remission Phenotype in Patients with Rheumatoid Arthritis?. (9th June 2015) - Gul, H.; Isorna Porto, M.J.; Ponchel, F.; Hensor, E.; Wakefield, R.; Emery, P.
Abstract : Background: Rheumatoid arthritis (RA) is an immune-mediated disease and primarily affects the synovium. The goal of treatment in RA is remission (1), however we do not routinely assess immunological markers or perform ultrasound imaging to define this. Objectives: We aimed to explore the clinical, imaging and immunological characteristics of RA patients in clinical remission (DAS28<2.6). Methods: A retrospective observational study was performed, using our inflammatory arthritis database. Patients were selected when fulfilling the inclusion criteria of RA diagnosis (1987 or 2010 ACR/EULAR criteria) and DAS28CRP≤3.2. The lowest observation of DAS28CRP after diagnosis and the availability of ultrasound data were prioritised. Disease/remission duration and treatment modality were not considered in this initial descriptive study. We collected data of: Tender and swollen joint counts, inflammatory markers, autoantibodies, patient-reported outcomes (PRO's), ultrasound and x-ray findings. Furthermore, T-cell subsets [naïve CD4+T-cells, Inflammation related cells (IRC), and regulatory T-cells (Treg)] were measured and analysed by advanced 8 colour flow-cytometry. Frequencies of T-cells were compared with reference range values obtained from 120 healthy controls. Results: We included 633 patients with a minimum DAS28CRP≤3.2 (mean 1.85/SD 0.67). The cohort was predominantly female (68.7%) and the mean age was 57.6 years. Of these, 513 were in DAS-defined remission. LDA was included as a control. In the remission group, 324 patients had ultrasound data available. Active synovitis, confirmed by positive Power Doppler signal was present in 43.2% (140/324) of patients. 76.2% (247/324) had evidence of grey scale (GS) changes >1 in ≥1 joint. For 51 patients where T-cell subset analysis was available, abnormal frequencies were observed in 11.8% of patients for naïve CD4+T-cells, 27.5% for IRC and 54.9% for Treg in the total cohort. For patients in remission, abnormal cell frequencies were seen in 8.7% (4/46), 23.9% (11/46) and 50% (23/46) for naïve, IRC and Treg's respectively. In LDA 65.3% (47/72) had evidence of Power Doppler synovitis and 86.1% (62/72) had GS changes >1 in ≥1 joint. Abnormal cell frequencies were found in 40% (2/5) of patients for naïve CD4 + T-cells, 60% (3/5) for IRC and all had abnormal Treg frequencies. The remission group had generally low levels of disability, functional and life impairment as expected. Conclusions: Despite being in clinical/DAS remission or LDA state, a substantial proportion of patients exhibit subclinical inflammation on ultrasound (higher for LDA). T-cell abnormalities were present in the majority. Current remission criteria are composite scores and do not measure inflammation directly (1). Identification of remission biomarkers could potentially help predict the ability to sustain remission and facilitate treatment withdrawal strategies, leading to a better understanding of what constitutes true remission. References: Saleem et al. Can remission be maintained with or without further drug therapy in rheumatoid arthritis? Clinical and experimental rheumatology. 2006 Nov-Dec; 24((6 Suppl 43)):S-33-36. Disclosure of Interest: None declared